Modelling of Static and Moving Objects: Digitizing Tangible and Intangible Cultural Heritage - Doulamis, Nikolaos D.; Doulamis, Anastasios; Ioannidis, Charalabos; Klein, Michael; Ioannides, Marinos (My University, 2017)
From the ancient library of Alexandria 2300 years ago, cultural collections have a common fundamental base; to gather, preserve and promote knowledge helping the intellectual and cognitive evolution of humanity. Nowadays the information revolution has given scientists, educators, researchers and individuals the ability not only to use a variety of digital libraries as a source of information but also to contribute to these libraries by uploading data that they create, leading to a massive production of digital data that we need to verify, manage, archive, preserve and reuse. Cultural heritage (CH) data is a category in digital libraries that needs our attention the most, because of their crucial role in helping us to interact with the past and learn, promote and preserve our cultural assets. Digital documentation of tangible and intangible heritage, data formats and standards, metadata and semantics, linked data, crowdsourcing and cloud, the use and reuse of data and copyright issues are the rising challenges that we try to address in this chapter, through literature research and best practice examples. At the end of this analysis, this chapter tries to predict the future of Digital Heritage Libraries, where 3D digital assets will be part of augmented, virtual and mixed reality experiences.
Keywords: 4D modelling; Tangible and intangible cultural heritage; 3D reconstruction; Semantics; Laban motion analysis